Investigating the Effects of Sample Conditioning on Nano-Apex Carbon Fiber Tips for Efficient Field Electron Emission - S. Alnawasreh; M. S. Mousa; A. N. Al-Rabadi (Jordan Journal of Physics, 2025)
: Carbon fibers represent a very interesting material for field electron emitters. While the preparation of sharp carbon fiber tips is very similar to the conventional method used for tungsten tips, much smaller apex radii can be obtained. Within the study presented here, such emitters have been prepared and tested using a standard field emission microscope (FEM). Various properties of these emitters were measured including the relationship between emitted electron current and applied voltage to the tip (the current-voltage characteristics) and the corresponding electron emission images. The field emission of carbon fibers has been studied via various methods of sample conditioning treatment; such as thermal relaxation process and cryogenic cooling. The performance of these tips was found to be dependent on the sample conditioning treatment. Keywords: Electrochemical etching; Field electron emission; Fowler-Nordheim plots; Carbon fiber tips; Vacuum-based analysis.